Synthesis of novel 4-arylidene-benzodiazepines using Cellulose@SiPr@Catechin@Fe3O4 - Tamila Shafaati; Mohammad Nikpassand; Masoud Mokhtary; Leila Zare Fekri (Results in Chemistry, 2024)
This research work describes the synthesis and characterization of Cellulose@SiPr@Catechin@Fe3O4 nanocomposite, a novel and effective nanocatalyst in the synthesis of 1,5-benzodiazepine derivatives by reaction of 1,2-phenylenediamine, Meldrum's acid and azo aldehydes. 1H NMR, 13C NMR, and FTIR spectral data and mass analyses characterized all products. The nanocatalyst was characterized by fourier transform infrared spectroscopy (FT-IR), field emission scanning electron microscope (FE-SEM), transmission electron microscope (TEM), Brunauer–Emmett–Teller (BET), X-ray powder diffraction (XRD), X-ray spectroscopy (EDX), vibrating sample magnetometry (VSM), and thermogravimetric analysis (TGA).